Rehabilitation Following ACL Repair with Internal Brace Ligament Augmentation in Female Gymnast: A Resident's Case Report - Colten Haack; Giorgio Zeppieri; Micheal W Moser (North American Sports Medicine Institute, 2024)
# Introduction Anterior Cruciate Ligament (ACL) injuries continue to be a major source of morbidity in gymnastics. The gold standard is to perform an ACL Reconstruction (ACLR). However, injuries to the proximal femoral attachment of the ACL have demonstrated an ability to regenerate. An alternative surgical intervention to the ACLR in this ACL tear subgroup is an ACL repair. The purpose of this case report is to provide a rehabilitation progression for a female gymnast after an ACL repair with Internal Brace Ligament Augmentation (IBLA). # Case Description The subject was a 16-year-old female who presented with a Sherman Type 1 proximal avulsion of her ACL. She underwent an ACL repair with IBLA. Physical therapy interventions followed a sequential and multi-phased approach based on time for tissue physiologic healing and individual progression. Patient reported outcomes including the International Knee Documentation Committee (IKDC), the Anterior Cruciate Ligament Return to Sport After Injury (ACL-RSI) and the Optimal Screening for Prediction of Referral and Outcome Yellow Flag (OSPRO-YF) were assessed in conjunction with isokinetic strength and hop performance testing to determine return to sport readiness. # Outcomes The subject completed 42 sessions over the course of 26 weeks in addition to a home exercise program. At return to sport, clinically meaningful improvement was observed in patient reported outcomes including the IKDC, ACL-RSI, and OSPRO-YF. Additionally, strength and hop performance surpassed established thresholds of clinical significance. The subject returned to sport at six months post-operatively. # Conclusion The subject in this case report returned to full participation in gymnastics six months after an ACL repair with internal bracing following a sequential and multi-phased rehabilitation. The primary ACL repair with IBLA appeared beneficial to this patient and could benefit from additional study in other athletes and athletic populations. # Level of Evidence Level 5